Perancangan Penerangan Jalan Umum Menggunakan Sistem Panel Surya di Padukuhan Masahan, Kelurahan Trirenggo: Indonesia - Mulyadi, Akmal Hasan; Putri, Divka Hanggita; Avrizal, Dhevanda Ashar Evrast; Herdiansyah, Daneswara Reiva; Purnomo, Agung (UII, 2026)
Solar-Powered Street Lighting (PJUTS) serves as a strategic solution to enhance safety, comfort, and community activities, particularly in rural areas with limited access to the national electricity grid. This study, conducted in Masahan Hamlet, Trirenggo Village, Bantul, aims to design an efficient, autonomous, and environmentally friendly PJUTS system. The methodology combines empirical field surveys (road conditions, lighting needs, light intensity, and pole spacing) with quantitative calculations of energy demand, solar panel capacity, battery storage, and light efficacy. The results indicate that the total energy demand of 720 Wh can be supplied by a 185 Wp solar panel system, where one 75 Wp module generates 225 Wh per day. Field implementation successfully installed three solar streetlights using LED lamps with 150 lumen/Watt efficiency, significantly improving community safety during nighttime. This study concludes that PJUTS can be effectively applied as a renewable energy-based lighting model for rural areas, while also supporting sustainability programs and reducing carbon emissions